2022
DOI: 10.1007/s10490-022-09814-z
|View full text |Cite
|
Sign up to set email alerts
|

Innovation through internationalization: A systematic review and research agenda

Abstract: In this paper we perform a systematic literature review of the diverse and somewhat fragmented current state of research on firms’ internationalization and innovation. We analyze 207 key works from 1989 through 2020 and synthesize them into an internationalization process framework that conceptually maps key internationalization-related antecedents and moderators that influence innovation behaviors and outcomes. Through an internationalization process framework, we categorize existing relevant studies into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 118 publications
(163 reference statements)
0
10
0
Order By: Relevance
“…3 had been named so, and the documents with the highest burst in Figure 10 had also reflected on this issue. From the analyses and the cases mentioned, it was concluded that the existence of a flexible strategy (as a model or roadmap) along with innovation resources to facilitate and accelerate the process of internationalization had received much attention in recent years as a necessity, this importance has been precisely emphasized byDu et al (2022) and Evers et al (2023), and they have also stated that international trade literature has seen a rapid growth of studies and despite this increase in research, the collection Knowledge about BMI and internationalization remains largely fragmented, thus putting theoretical and empirical advances in this field at risk. Although past studies on BMI have multiplied in the mainstream business literature, none have been conducted in the context of international business.…”
Section: Discussionmentioning
confidence: 99%
“…3 had been named so, and the documents with the highest burst in Figure 10 had also reflected on this issue. From the analyses and the cases mentioned, it was concluded that the existence of a flexible strategy (as a model or roadmap) along with innovation resources to facilitate and accelerate the process of internationalization had received much attention in recent years as a necessity, this importance has been precisely emphasized byDu et al (2022) and Evers et al (2023), and they have also stated that international trade literature has seen a rapid growth of studies and despite this increase in research, the collection Knowledge about BMI and internationalization remains largely fragmented, thus putting theoretical and empirical advances in this field at risk. Although past studies on BMI have multiplied in the mainstream business literature, none have been conducted in the context of international business.…”
Section: Discussionmentioning
confidence: 99%
“…To engage in exploratory innovations as a response to the dynamic environment, diversity in technological knowledge and capabilities is the key. Collaborations with external technology providers will be beneficial for firms to obtain and access new and diversified knowledge sets and capabilities to innovate (Du et al, 2023;Wang, 2021). In the case when technological uncertainty increases, hierarchy will be a less preferred option, for hierarchical control makes it less flexible to switch over to appropriate partners' technological capabilities and thereby increases the risk of being locked into obsolete technologies (Sirmon et al, 2007;Wang, 2021;Yang et al, 2022).…”
Section: Negative Moderating Effect Of Dynamic Environmentsmentioning
confidence: 99%
“…To engage in exploratory innovations as a response to the dynamic environment, diversity in technological knowledge and capabilities is the key. Collaborations with external technology providers will be beneficial for firms to obtain and access new and diversified knowledge sets and capabilities to innovate (Du et al. , 2023; Wang, 2021).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations